2022
DOI: 10.21203/rs.3.rs-1140166/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does Government Intervention Affect CO2 Emission Reduction Effect of Producer Services Agglomeration? Empirical Analysis Based on Spatial Dubin Model and Dynamic Threshold Model

Abstract: Achieving carbon peak and carbon neutrality is an inherent requirement for countries to promote green recovery and transformation of the global economy after the COVID-19 pandemic. As "a smoke-free industry", its agglomeration may have significant impacts on CO2 emission reduction. This study uses nightlight data to calculate the CO2 emissions of 268 cities in China from 2005 to 2017 and then employs dynamic spatial Dubin model and intermediary effect model to explore the impact and transmission mechanism of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…For example, previous research has drawn attention to the environmental pollutant treatment technology (36) and the food supply chain's waste problem (37) On the other hand, from the perspective of the output of ESI, there is also evidence highlighting the negative impact of the pandemic on ESI. For example, a survey of 526 companies in Norway showed that the average level of firms' adoption of environmental innovations had dropped significantly due to the COVID-19 pandemic (41). The COVID-19 pandemic has affected the implementation of plastic reduction policies in Europe and around the world, thus leading to an increase in plastic waste, which harms the environment and human health (42).…”
Section: Impact Of the Covid-pandemic On Esi And Its E Ciencymentioning
confidence: 99%
“…For example, previous research has drawn attention to the environmental pollutant treatment technology (36) and the food supply chain's waste problem (37) On the other hand, from the perspective of the output of ESI, there is also evidence highlighting the negative impact of the pandemic on ESI. For example, a survey of 526 companies in Norway showed that the average level of firms' adoption of environmental innovations had dropped significantly due to the COVID-19 pandemic (41). The COVID-19 pandemic has affected the implementation of plastic reduction policies in Europe and around the world, thus leading to an increase in plastic waste, which harms the environment and human health (42).…”
Section: Impact Of the Covid-pandemic On Esi And Its E Ciencymentioning
confidence: 99%